Local salvage therapy for late (≥2 years) metastatic and local relapse of renal cell cancer is a potentially curative treatment irrespective of the site of recurrence - Grüllich, Carsten; Vallet, Sonia; Hecht, Christopher; Duensing, Stefan; Hadaschik, Boris; Jäger, Dirk; Hohenfellner, Markus; Pahernik, Sascha (Urologic oncology, 2016)
Objective - The primary treatment approach to locoregional renal cell carcinoma (RCC) is surgical resection. Most relapses occur within the first 2 years but some patients experience late recurrences. Surgical resection of oligometastatic disease may be considered a curative option for relapsed RCC. However, limited data are available of long-term follow-up of late relapse regarding treatment choice. - Patients and methods - We identified 104 patients with RCC from our database, who relapsed after≥2 years from resection of their primary tumor. Median age at primary diagnosis was 61 years and sex distribution was F:M = 40:64. Histology was clear cell, n = 103 and papillary, n = 1. Sites of relapse were local, n = 14 (13.4%); lung only, n = 25 (24.0%); or extrapulmonary, n = 65 (62.5%). Treatment at first relapse was local therapy (LT) in n = 60 (57.7%) patients, of these, n = 55 patients had surgery done and n = 5 patients had underwent radiotherapy. Systemic therapy was used in n = 9 (8.7%) patients. Overall, 35 patients received best supportive care (33.7%). - Results - We found a median overall survival (OS) of 49.8 months (95% CI: 29.3-70.2) and a progression-free survival (PFS) of 21.6 months (95% CI: 12.6-30.5) for all patients. Patients receiving LT had a median OS of 99.9 months (95% CI: 77.2-122.6) and a PFS of 31.1 months (95% CI: 21.5-40.7). Patients treated with systemic therapy, in turn, had an OS of 21.1 months (95% CI: 8.4-33.8) and a PFS of 4 months (95% CI: 1.0-6.2). Patients who received best supportive care had an OS of 10 months (95% CI: 1.3-18.7). This difference was highly significant (log rank for PFS: P<0.001; log rank for OS: P<0.003). Subgroup analysis of the LT group showed a superior outcome for local relapses (OS: not reached, PFS: 61.4mo [95% CI: 28.5-9.2]) compared to visceral relapses (OS: 35.5mo [95% CI: 17.9-53.1], PFS: 21.1mo [95% CI: 19.2-22.9]). - Conclusion - Local salvage therapy should be considered the first therapeutic option in late relapse of RCC irrespective of the site of relapse.